Femoral neck system with an additional cannulated screw for the treatment of elderly femoral neck fractures: a retrospective study - Yu, Xiang; Zhang, Jun; Li, Yu-Zhi; Li, Xiao-Kai; Chen, Fan-Cheng; Hu, Hong-Kui; Li, Xu; Liu, Bing-Li; Yu, Bao-Qing; Ao, Rong-Guang (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveTo compare the clinical efficacy of the femoral neck system (FNS) alone versus FNS combined with an additional cannulated compression screw (CCS) for treating elderly patients (aged 65–75) with Garden I–III femoral neck fractures.MethodsThis retrospective study analyzed 126 patients treated between January 2020 and December 2022. Patients were divided into an FNS group (n = 60) and an FNS+CCS group (n = 66). Key outcomes included operative time, intraoperative blood loss, fluoroscopy frequency, fracture healing time, femoral neck shortening, complications, VAS pain scores, and Harris hip scores at final follow-up.ResultsThe two groups showed no significant differences in baseline characteristics. While intraoperative blood loss was comparable, the FNS+CCS group had significantly longer operative times and required more fluoroscopies. All patients were followed for an average of 14.1 months. The FNS+CCS group demonstrated a significantly shorter fracture healing time and a lower incidence of femoral neck shortening at final follow-up. Although VAS scores were similar between groups, the FNS+CCS group achieved significantly higher Harris hip scores. The incidence of complications did not differ significantly.ConclusionFor elderly patients with femoral neck fractures, FNS fixation augmented with a CCS offers significant advantages over FNS alone, including accelerated fracture healing and superior functional recovery of the hip joint, despite a longer operative time.